2022
DOI: 10.1002/ajhb.23789
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension among the indigenous population in North‐East India: Is this a consequence of “nutritional transition”?

Abstract: Objectives: This article aims to understand the influence of residential status on the prevalence of cardiovascular disease (CVD) risk factors among adult Angami Naga of Nagaland.Methods: A total number of 194 (100 rural and 94 urban) adult Angami Naga participated in the study. Blood pressure, both systolic and diastolic, was measured for each participant. Nutritional status was evaluated through body mass index. Metabolic health was measured through waist circumference, waist-hip ratio and percent body fat (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
1
0
0
Order By: Relevance
“…The evolutionary significance of sex differences in anthropometric and physiological measures is still unclear, as the trend is not comparable across human populations. However, in line with the present study, sex differences in physiological attributes were also reported in previous studies [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The evolutionary significance of sex differences in anthropometric and physiological measures is still unclear, as the trend is not comparable across human populations. However, in line with the present study, sex differences in physiological attributes were also reported in previous studies [ 17 , 21 23 ].…”
Section: Discussionsupporting
confidence: 93%